TRANSITION TO EXCHANGE PRICING OF GAS: INFLUENCE ON BRANCH OF HEAT SUPPLY - V. Brents (Publishing House of the State University of Management, 2017)
In article exchange pricing on gas, in the current conditions is considered: introduction history is specified, the current statistics is presented. On the basis of the provided statistics the difference of the prices at different types of pricing for gas is revealed. Also the main consumers of gas on whom exchange pricing will exert impact are provided in article. It is defined that for branch of heat supply transition from gas is inexpedient. Also influence of exchange prices of tariffs for thermal energy is revealed.